The Black Bruins : the remarkable lives of UCLA's Jackie Robinson, Woody Strode, Tom Bradley, Kenny Washington, and Ray Bartlett - Johnson, James W., 1938- (University of Nebraska Press, 2017)
"The intertwined story of five influential African American athletes who came together as teammates at UCLA in the 1930s"-- Provided by publisher.
Keywords: Robinson, Jackie, -- 1919-1972.; Strode, Woody.; Bradley, Tom, -- 1917-1998.; Washington, Kenny, -- 1918-1971.; Bartlett, Ray, -- 1919-2008.; University of California, Los Angeles -- Sports -- History -- 20th century.; Washington, Kenny, -- 1918-1971; Strode, Woody; Robinson, Jackie, -- 1919-1972; Bradley, Tom, -- 1917-1998; University of California, Los Angeles; African American athletes -- United States -- Biography.; Discrimination in sports -- United States -- History -- 20th century.; Racism in sports -- United States -- History -- 20th century.; African American athletes -- California, Southern -- Social conditions -- 20th century.; African Americans -- California, Southern -- Social conditions -- 20th century.; Race relations -- History -- 20th century.; Racism -- California, Southern -- 20th century.; Sportifs noirs américains -- États-Unis -- Biographies.; Discrimination dans les sports -- États-Unis -- Histoire -- 20e siècle.; Racisme dans les sports -- États-Unis -- Histoire -- 20e siècle.; Sportifs noirs américains -- Californie (Sud) -- Conditions sociales -- 20e siècle.; Noirs américains -- Californie (Sud) -- Conditions sociales -- 20e siècle.; Relations raciales -- Histoire -- 20e siècle.; Racisme -- Californie (Sud) -- 20e siècle.; SPORTS & RECREATION -- History.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies.; HISTORY -- United States -- State & Local -- West (AK, CA, CO, HI, ID, MT, NV, UT, WY); Racism; Race relations; African Americans -- Social conditions; African American athletes -- Social conditions; Southern California; African American athletes; Discrimination in sports; Racism in sports; Sports; United States; 1900-1999; collective biographies.; Biographies; History; Biographies.